The Paradigm Wars: Is MMR Really a Solution? - Williams, Ryan Thomas (American Journal of Trade and Policy, 2020)
Educational research has several competing views of the social sciences, and these are often referred to as paradigms. Hammersley (2013, p. 13) portrays paradigms as ‘not simply methodologies; they are ways of looking at the world, different assumptions about what the world is like and how we can understand or know about it’.  The paradigm wars’ boils down to a simple conflict between academics and scholars of qualitative and quantitative research which concerns the relative merits of the different perspectives. In the 1980s, the objectivity-seeking quantitative researcher diminished, whilst, post positivists, interpretivists, and critical theorists flourished throughout this same period. Mixed methods research (MMR) combines elements of both qualitative and quantitative approaches and has often been branded as a ‘transformative paradigm’. The importance of MMR means that the author can combine knowledge sets and move away from one’s allegiance to a particular research perspective. This review of literature will examine the paradigms that are commonly associated with education research. There is an active debate in the research community on the paradigms wars, and this will also be examined in relation to MMR.
Keywords: MMR; Paradigm wars; Educational research